ISO 14001 - Some international perspectives - Herreborg Jorgensen, tine (Malaysian Journal of Science, 2004)
The aim of this paper is to discuss a number of issues related to ISO 14001, the international standard for environmental management systems (EMS). The standard is a process standard that leaves room for interpretation at company level as well as among lead auditors from certifying bodies. The paper questions whether the interpretation of the standard is uniform both at national and international levels. The paper also suggests changes of ISO 14001 in order to formulate more clear demands of environmental improvements, to include demand for publication of an environmental report and to include product focus more clearly. Secondly the paper briefly presents a cases study of four companies in the automotive industry in South Africa, related to the discussions of ISO 14001 and compliance with environmental regulation